Method for improving pre-lithium silica gas production based on aluminum phosphate modification and secondary carbon coating

Through aluminum phosphate modification and secondary carbon coating technology, the problems of silicon oxygen batteries in battery capacity and stability are solved, the gas production capacity and battery performance of silicon oxygen batteries are improved, the residual alkali quantity is reduced, and the further development is achieved High battery efficiency.

CN119160923AInactive Publication Date: 2024-12-20SHANDONG SOLIDE NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411631897.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing silicon oxygen batteries have shortcomings in battery capacity, gas resistance, stability and primary effectiveness, especially when the material reacts with water under the water system, the coating layer is incomplete and the residual alkali is high.

Method used

Using a method based on aluminum phosphate modification and secondary carbon coating, the primary carbon coating and prelithiation treatment is carried out, and then the aluminum phosphate solution is mixed with ammonium phosphate solution, stirring and reacting with the silicon oxide raw material to form aluminum phosphate modification The composite material is then coated with secondary carbon to improve the gas production capacity of silicon oxygen batteries.

Benefits of technology

The gas production capacity of prelithium silicon oxygen batteries is significantly improved, the residual alkali amount is reduced, and the first effect and stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention is suitable for the technical field of silicon-oxygen gas production, and provides a method for improving pre-lithiation silicon-oxygen gas production based on aluminum phosphate modification and secondary carbon coating, and the method comprises the following steps: S1, primary carbon coating and pre-lithiation treatment; s2, aluminum phosphate modification: S21, preparing an ammonium phosphate solution; s22, preparing an aluminum phosphate solution; s23, adding the ammonium phosphate solution into the aluminum phosphate solution, and stirring and mixing to obtain a mixed solution 1; s24, adding the pre-lithiated and washed silicon oxide raw material into the mixed solution 1 to obtain a mixed solution 2; s25, stirring the mixed solution 2 for 6-18 hours according to the frequency of 50Hz, and performing suction filtration to obtain a solid; and S26, drying the solid in a vacuum dryer at 95 DEG C for 3-9 hours to finally obtain the silica composite material coated with aluminum oxide. And S3, taking the aluminum phosphate modified composite material in the S2, coating a carbon source, carrying out secondary carbon coating, and packaging according to 40kg / batch. According to the method, the pre-lithium silica gas production capacity is greatly improved, the residual alkali amount is reduced, and the first effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicon-oxygen gas production, and specifically to a method for improving pre-lithium silicon-oxygen gas production based on aluminum phosphate modification and secondary carbon coating. Background Art

[0002] With the popularity of smart wearables and digital products in every household, the pursuit of longer battery life has become a common perception among the public. With the rise of electric vehicles / drones, the requirements for battery performance and life are getting higher and higher. Batteries can be divided into different types according to different materials. Silicon oxygen batteries are one of the main types of batteries currently available.

[0003] Most of the existing silicon-oxygen batteries have low battery capacity, high pH values, poor gas production resistance, and poor stability. In the water system, the material reacts with water, the coating layer is incomplete, the initial efficiency is low, and the residual alkali is high. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating to solve the problems in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating, comprising the following steps: S1, initial carbon coating and pre-lithiation treatment: Taking silicon oxygen raw material and coated carbon source, performing initial carbon coating to obtain carbon coated silicon oxygen material, then performing pre-lithiation treatment to obtain pre-lithiation silicon oxygen, and then washing with water; S2, aluminum phosphate modification: S21, preparing ammonium phosphate solution; S22, preparing aluminum phosphate solution; S23, adding the ammonium phosphate solution to the aluminum phosphate solution and stirring and mixing to obtain a mixed solution 1; S24, adding the pre-lithiation and washed silicon oxide raw material to the mixed solution 1 to obtain a mixed solution 2; S25, stirring the mixed solution 2 at a frequency of 50 Hz for 6 to 18 hours, and then filtering to obtain a solid; S26, placing the solid in a vacuum dryer at 95° C. and drying for 3 to 9 hours, finally obtaining a silicon-oxygen composite material coated with aluminum oxide; S3, taking the aluminum phosphate-modified composite material and coated carbon source in S2, performing secondary carbon coating, and packaging at 40 kg / batch.

[0006] Preferably, the ammonium phosphate solution in S21 is prepared by mixing ammonium phosphate with pure water, and the content of ammonium phosphate in the ammonium phosphate solution is 1 to 8 wt %.

[0007] Preferably, the aluminum phosphate solution in S22 is prepared by mixing aluminum phosphate and ethanol, and the content of aluminum phosphate in the aluminum phosphate solution is 0.05-2 wt %.

[0008] Preferably, the washed silicon oxide raw material after pre-lithiation in S24 is immersed in the mixed solution 1 at a material weight ratio of 1:3.

[0009] Preferably, the S26 coated alumina is an Al2O3 coating layer obtained by heat treating aluminum hydroxide at 95°C.

[0010] Preferably, the coated carbon source is graphite powder, carbon nanotubes or graphene.

[0011] Preferably, the thickness of the carbon coating layer of the primary carbon coating is 8 to 15 nm, and the thickness of the carbon coating layer of the secondary carbon coating is 3 to 6 nm.

[0012] The present invention has at least the following beneficial effects: The method for improving pre-lithium silicon-oxygen gas production based on aluminum phosphate modification and secondary carbon coating provided by the present invention greatly improves the pre-lithium silicon-oxygen gas production capacity, reduces the residual alkali amount, and improves the initial effect after aluminum phosphate modification and secondary carbon coating. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] The present invention provides a method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating, comprising the following steps: S1, initial carbon coating and pre-lithiation treatment: Taking silicon oxygen raw material and coated carbon source, performing initial carbon coating to obtain carbon coated silicon oxygen material, then performing pre-lithiation treatment to obtain pre-lithiation silicon oxygen, and then washing with water; S2, aluminum phosphate modification: S21, preparing ammonium phosphate solution; S22, preparing aluminum phosphate solution; S23, adding the ammonium phosphate solution to the aluminum phosphate solution and stirring and mixing to obtain a mixed solution 1; S24, adding the pre-lithiation and washed silicon oxide raw material to the mixed solution 1 to obtain a mixed solution 2; S25, stirring the mixed solution 2 at a frequency of 50 Hz for 6 to 18 hours, and then filtering to obtain a solid; S26, placing the solid in a vacuum dryer at 95° C. and drying for 3 to 9 hours, finally obtaining a silicon-oxygen composite material coated with aluminum oxide; S3, taking the aluminum phosphate-modified composite material and coated carbon source in S2, performing secondary carbon coating, and packaging at 40 kg / batch.

[0015] Among them, the ammonium phosphate solution in S21 is prepared by ammonium phosphate and pure water, and the content of ammonium phosphate in the ammonium phosphate solution is 1-8wt%; the aluminum phosphate solution in S22 is prepared by aluminum phosphate and ethanol, and the content of aluminum phosphate in the aluminum phosphate solution is 0.05-2wt%; in S24, the silicon oxide raw material washed after pre-lithiation is immersed in the mixed solution 1 at a material weight ratio of 1:3.

[0016] Among them, S26 coated alumina is an Al2O3 coating layer obtained by heat treating aluminum hydroxide at 95°C; the coated carbon source is graphite powder, carbon nanotubes or graphene; the thickness of the carbon coating layer of the primary carbon coating is 8 to 15 nm, and the thickness of the carbon coating layer of the secondary carbon coating is 3 to 6 nm.

[0017] The present invention configures ammonium phosphate and aluminum phosphate into a low-concentration solution in a certain ratio, and soaks the pre-lithiation silicon-oxygen composite material for 12 hours, so that the free Li ions of the pre-lithiation silicon-oxygen composite material are combined with phosphate ions and retained in the product, thereby reducing residual alkali; at the same time, the defect positions and surface of the pre-lithiation silicon-oxygen composite material react to form Al(OH)3 precipitation, and then the aluminum hydroxide is oxidized into aluminum oxide by heating to achieve aluminum phosphate modification, and the gas production capacity of the pre-lithiation silicon-oxygen is improved through two carbon coatings.

[0018] Based on the above technical solution, the present invention provides the following partial embodiments:

[0019] Example 1 (1) taking silicon oxide raw materials and graphite powder, performing initial carbon coating to obtain carbon-coated silicon oxide material, wherein the thickness of the carbon coating layer of the initial carbon coating is 8 nm, and then performing pre-lithiation treatment to obtain pre-lithium silicon oxide, and then washing with water; (2) Preparation of ammonium phosphate solution: Take 5g of ammonium phosphate and dissolve it in 45g of pure water. Wait until it is completely dissolved to make ammonium phosphate solution and set it aside for later use.

[0020] (3) Preparation of aluminum phosphate solution: Take 2 g of aluminum phosphate and dissolve it in 298 g of ethanol. Use a stirrer to stir at a frequency of 30 Hz for 30 minutes to prepare an aluminum phosphate solution, and set it aside for later use.

[0021] (4) Preparation of mixed solution of ammonium phosphate and aluminum phosphate solution: The ammonium phosphate solution obtained in (2) was added to the aluminum phosphate solution obtained in (3), and the mixture was stirred at a frequency of 30 Hz for 10 min to obtain a mixed solution 1.

[0022] (5) The pre-lithiation and washed silicon oxide raw material is added to the mixed solution 1 obtained in (4) to obtain a mixed solution 2.

[0023] (6) The beaker containing the mixed solution 2 is sealed, the stirring frequency is adjusted to 50 Hz, and the mixture is stirred for 12 hours for coating. After the time is up, the coated solid is filtered out using a suction pump to obtain a pre-lithiated silicon-oxygen composite material containing Al(OH)3 to obtain a solid.

[0024] (7) The solid was placed in a vacuum dryer at 95°C and dried for 6 hours to obtain a silicon-oxygen composite material coated with aluminum oxide; (8) The aluminum phosphate-modified composite material and graphite powder in (7) are subjected to secondary carbon coating. The thickness of the carbon coating layer of the secondary carbon coating is 3 nm and the composite material is packaged at 40 kg / batch.

[0025] Example 2 The difference from Example 1 is: In step (1), the coated carbon source is carbon nanotubes, and the thickness of the carbon coating layer of the primary carbon coating is 10 nm; in step (8), the coated carbon source is carbon nanotubes, and the thickness of the carbon coating layer of the secondary carbon coating is 5 nm.

[0026] The aluminum phosphate content in the aluminum phosphate solution of step (2) is 0.33 wt %, and the rest is the same as in Example 1.

[0027] Example 3 The difference from Example 1 is: In step (1), the coating carbon source is graphene, and the thickness of the carbon coating layer of the primary carbon coating is 15 nm; in step (8), the coating carbon source is graphene, and the thickness of the carbon coating layer of the secondary carbon coating is 6 nm.

[0028] The aluminum phosphate content in the aluminum phosphate solution of step (2) is 1 wt %, and the rest is the same as in Example 1.

[0029] Example 4 The difference from Example 1 is: In step (1), the coated carbon source is graphite powder, and the thickness of the carbon coating layer of the primary carbon coating is 8 nm; in step (8), the coated carbon source is graphene, and the thickness of the carbon coating layer of the secondary carbon coating is 6 nm.

[0030] The ammonium phosphate content in the ammonium phosphate solution of step (2) is 5 wt %, and the rest is the same as in Example 1.

[0031] Example 5 The difference from Example 1 is: In step (1), the coated carbon source is carbon nanotubes, and the thickness of the carbon coating layer of the primary carbon coating is 10 nm; in step (8), the coated carbon source is graphite powder, and the thickness of the carbon coating layer of the secondary carbon coating is 3 nm.

[0032] The ammonium phosphate content in the ammonium phosphate solution of step (2) is 15 wt %, and the rest is the same as in Example 1.

[0033] Example 6 The difference from Example 1 is: In step (1), the coated carbon source is graphene, and the thickness of the carbon coating layer of the primary carbon coating is 15 nm; in step (8), the coated carbon source is carbon nanotubes, and the thickness of the carbon coating layer of the secondary carbon coating is 6 nm.

[0034] In step (6), the stirring coating time was changed to 6 h, and the rest was the same as in Example 1.

[0035] Example 7 The difference from Example 1 is: In step (1), the coating carbon source is graphene, and the thickness of the carbon coating layer of the primary carbon coating is 15 nm; in step (8), the coating carbon source is graphene, and the thickness of the carbon coating layer of the secondary carbon coating is 6 nm.

[0036] In step (6), the stirring coating time was changed to 18 h, and the rest was the same as in Example 1.

[0037] Example 8 The difference from Example 1 is: In step (1), the coated carbon source is graphite powder, and the thickness of the carbon coating layer of the primary carbon coating is 15 nm; in step (8), the coated carbon source is graphene, and the thickness of the carbon coating layer of the secondary carbon coating is 3 nm.

[0038] In step (7), the mixture is placed in a vacuum dryer at 95° C. and dried for 3 h. The rest is the same as in Example 1.

[0039] Example 9 The difference from Example 1 is: In step (1), the coated carbon source is graphene, and the thickness of the carbon coating layer of the primary carbon coating is 8 nm; in step (8), the coated carbon source is carbon nanotubes, and the thickness of the carbon coating layer of the secondary carbon coating is 6 nm.

[0040] In step (7), the mixture is placed in a vacuum dryer at 95° C. and dried for 9 h. The rest is the same as in Example 1.

[0041] A series of relevant performance tests were carried out on the products prepared in the above Examples 1-9, and the results are as follows: ①. The initial carbon coating stability is 3±0.5wt%, and the specific surface area is <2.

[0042] ②. After aluminum phosphate modification + two carbon coatings, the gas production of the product at room temperature is <0.5mL / g for 168h; residual alkali ≤1000ppm; silicon grains ≤6nm; 1.5v capacity increased by 40mAh / g (1390mAh / g), and the first efficiency increased by 1.5% (91.5%); 0.8v capacity increased by 30mAh / g (1250mAh / g), and the first efficiency increased by 1.5% (821.5%).

[0043] In summary, the present invention uses aluminum phosphate modification and two carbon coatings to greatly improve the pre-lithium silicon oxygen gas production capacity, reduce the residual alkali content, and improve the initial effect.

[0044] The above shows and describes the basic principles, main features and advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and that the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.

[0045] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating, characterized in that: The following steps are involved: S1, initial carbon coating and pre-lithiation treatment: Taking silicon oxygen raw material and coated carbon source, performing initial carbon coating to obtain carbon coated silicon oxygen material, then performing pre-lithiation treatment to obtain pre-lithiation silicon oxygen, and then washing with water; S2, aluminum phosphate modification: S21, preparing ammonium phosphate solution; S22, preparing aluminum phosphate solution; S23, adding the ammonium phosphate solution to the aluminum phosphate solution and stirring and mixing to obtain a mixed solution 1; S24, adding the pre-lithiation and washed silicon oxide raw material to the mixed solution 1 to obtain a mixed solution 2; S25, stirring the mixed solution 2 at a frequency of 50 Hz for 6 to 18 hours, and then filtering to obtain a solid; S26, placing the solid in a vacuum dryer at 95° C. and drying for 3 to 9 hours, and finally obtaining a silicon-oxygen composite material coated with aluminum oxide; S3, taking the aluminum phosphate-modified composite material and coated carbon source in S2, performing secondary carbon coating, and packaging at 40 kg / batch.

2. The method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating according to claim 1, characterized in that: The ammonium phosphate solution in S21 is prepared by mixing ammonium phosphate with pure water, and the content of ammonium phosphate in the ammonium phosphate solution is 1-8 wt %.

3. The method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating according to claim 1, characterized in that: The aluminum phosphate solution in S22 is prepared by mixing aluminum phosphate and ethanol, and the content of aluminum phosphate in the aluminum phosphate solution is 0.05-2 wt %.

4. The method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating according to claim 1, characterized in that: The washed silicon oxide raw material after pre-lithiation in S24 is immersed in the mixed solution 1 at a material weight ratio of 1:

3.

5. The method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating according to claim 1, characterized in that: The S26 coated alumina is an Al2O3 coating layer obtained by heat treating aluminum hydroxide at 95°C.

6. The method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating according to claim 1, characterized in that: The coated carbon source is graphite powder, carbon nanotube or graphene.

7. The method for improving pre-lithium silicon oxygen gas production based on aluminum phosphate modification and secondary carbon coating according to claim 1, characterized in that: The thickness of the carbon coating layer of the primary carbon coating is 8-15 nm, and the thickness of the carbon coating layer of the secondary carbon coating is 3-6 nm.

Citation Information

Patent Citations

  • Preparation method and application of silicon-based composite material slurry

    CN112201779A

  • Alumina-coated silica composite material and preparation method thereof

    CN118791028A

  • High-first-efficiency and high-rate silicon-based negative electrode material and preparation method therefor

    WO2022257311A1